Impacto da utilização de diferentes critérios clínicos diagnósticos na prevalência, associação causal e extensão da doença periodontal - Alessandra Neves Guimaraes (2005)
The aim of the present study was to evaluate the impact of different diagnostic criteria in the prevalence, causal relationship significance and extent of periodontal disease, due to the lack of uniformity in literature to define the disease. For this, 340 periodontal exams of a data base that were been assessed by the same examiner in three public schools and two public health services in the west region of Belo Horizonte, Brazil, were used. The subjects examined were from both gender, ages between 18 to 55, from heterogenic ethnic group, and low socioeconomic level. Methodologically the following diagnostic criteria were applied: (I) 1 site with AL (attachment loss) 4 mm and PD (probing depth) 4 mm (AAP, 2000); (II) AL 5 mm in four or more sites, and 1 of them with PD 4 mm (Beck, 1990); (III) AL 6 mm in 2 or more teeth and 1 site with PD 5 mm (Machtei, 1992); (IV) four or more teeth with at least 1 site with PD 4 mm and AL 3 mm (L¾pez et al., 2002). Prevalences for the different criteria I, II, III and IV, were respectively, 65,3%, 23,8%, 16,5%, 51,5%. There was a good reliability between parameters I and IV (Kappa test 0,721) and also between II and III (Kappa test 0,719). There was a considerable variability in the significance of the association between periodontal disease and independent variables of interest (smoking, anxiety, cardiovascular disease and diabetes) for each diagnostic criteria. The values of periodontal disease extent, revealed a considerable variability for the local form of periodontal disease (13,2% to 55,9%) for each criteria; in contrast, a smaller variability was observed for the generalized form of the disease (5,9% to 9,7%). In conclusion, this study showed that there is a significant impact of the criteria used to asses the prevalence of periodontal disease, in addition that the second criteria was the most similar to the prevalence usually referred by literature.